Determinants of Electronic Customer Loyalty on TikTok Shop: Roles of Quality Experience Satisfaction and EWOM - Syakir Abdul Wadud; Mahrinasari; Miguna Astuti (Yayasan Ilomata, 2026)
This study investigates electronic customer loyalty in video-based social commerce by analyzing TikTok Shop users in Jakarta, Indonesia. Prior studies on e-loyalty and TikTok Shop contexts have predominantly examined partial relationships such as the direct effects of electronic service quality (ESQ) or electronic word of mouth (eWOM) on loyalty often treating electronic customer experience (ECE) and electronic customer satisfaction (ECS) as isolated or sequential predictors rather than integrating them within a comprehensive structural model. In contrast, this study develops and empirically tests an integrated framework that simultaneously incorporates ESQ, ECE, ECS, and eWOM, while also explicitly distinguishing ECE as a process-based construct reflecting interactive user engagement and ECS as an outcome-based evaluative judgment in the formation of loyalty. Using a cross-sectional survey of 235 TikTok Shop users and applying PLS-SEM analysis, the results demonstrate that ESQ and ECE have significant positive effects on electronic customer loyalty. Furthermore, bootstrapped mediation analysis reveals that the indirect effects of ECS and eWOM on loyalty are not statistically significant, as indicated by their respective path coefficients, t-values, p-values, and 95% confidence intervals that include zero, thereby confirming the absence of meaningful mediation effects. These findings suggest that loyalty in video-based social commerce is more strongly driven by consistent service performance and interactive experiential processes than by post-purchase evaluations or communicative diffusion alone. The study contributes empirically by clarifying the roles of process- and outcome-based constructs within an integrated e-loyalty model in the context of emerging video-commerce ecosystems in Southeast Asian digital markets.